Effects of Regional Goverment Expenditures on the Education, Health, and Infrastructure Sector on Economic Growth in West Kalimantan Period 2009-2013 - B1011131060, kamisah (Fakultas Ekonomi dan Bisnin Universitas Tanjungpura, 2017)
ABSTRACT Local government sector expenditure on education, health and infrastructure against economic growth. Sustainable development became a major challenge in the global community as well the area at his time. Each region has a goal of boost the growth of its economy. Economic growth is one of the variables of the economy in a region that is seen from the indicator of comsumption, investment, export an import expenditure, thus creating economic growth in a region that is on the rise. The intended area of goverment spending is spending on the education sector, health, and infrastructure. The third is a sector that is very important for the development process of an area. Government spending over education, health, and infrastructureagainst economic growth can not be directly perceived within the short term but will be felt in the long term of time. Test and analyze the influence of the local government sector of education, health and infrastructure against economic growth in the province of West Kalimantan The data used in this research is secondary data. Secondary data used is the data panel which is a merger between the data of cross section and time series data. Using the method of data analysis in this study uses panel data regression analysis with PLS (Pooled Least Square) and using eviews application 9. The results of educational research the positive and significant effect against economic growth with a probability of 0.0000, health is also positive and significant effect against economic growth with a probability of 0.0000. While the positive effect of the infrastructure but not significant with probability more than 0.05 or 0.8065. Keywords: education, health, infrastructure, and economic growth